Cultural Strategies of Abdi Dalem in The Global Era in Achieving Welfare - Sulistyowati Sulistyowati (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2013)
The article aims at examining cultural strategies of Javanese community, particularly those of the abdi dalem (royal official), in achieving welfare. It is inevitable for the abdi dalem, who has existed for more than one century in Javanese community, to face the changes of era (global era). Javanese cultural values which are believed and accepted as the guidance in daily behaviour are opposed to the values in globalization that worship material as the highest value. The behaviour of abdi dalem as cultural actors holding thight to Javanese cultural values or Javanese logic (logika kejawen) in their evervdav lives will be understood in context to see their fiexibilties in responding to any changes accured around them. Through this understanding, the research is aimed to uncover the functions of cultural values as cultural identity and strategic function in promoting the sustainability of public support (abdi dalem) within the globalization challenges. Hopefully, the result of this research will be useful for the policy makers as well as the community to reveal the positive values of Javanese culture to adapt to the changing era. To obtain the objectives of the research, qualitative method is adopted. Methods of data collection used are participant observation and in-depth interviews. The informants selected in this study are the abdi dalem of Yogyakarta Palace. Through the interpretative approach of the symbols of abdi dalem behavior inexpressible that devotion to the king for ngalap berkah, simple lifestyles and the harmony principle is offered by abdi dalem to achieve welfare within the globalization challenges.